60.3k views
1 vote
Evaluate -y+(-z)+7.99−y+(−z)+7.99minus, y, plus, left parenthesis, minus, z, right parenthesis, plus, 7, point, 99 where y = 1.46y=1.46y, equals, 1, point, 46 and z = 3.82z=3.82z, equals, 3, point, 82.

User KFleischer
by
5.6k points

2 Answers

3 votes

Answer:

2.71

Step-by-step explanation:

User Mica
by
5.1k points
3 votes

The solution is
2.71

Step-by-step explanation:

The expression is
-y+(-z)+7.99

where
y=1.46 and
z=3.82

To determine the value of the expression, let us substitute the value of y and z in the expression.

Thus, the expression becomes,


-1.46+(-3.82)+7.99

Simplifying, we have,


-1.46-3.82+7.99

Adding the negative terms, we get,


-5.28+7.99

Adding, we have,


2.71

Thus, the solution is
2.71

User John Grayson
by
5.1k points